2017
DOI: 10.1002/mc.22605
|View full text |Cite
|
Sign up to set email alerts
|

Persistent phosphorylation at specific H3 serine residues involved in chemical carcinogen‐induced cell transformation

Abstract: Identification of aberrant histone H3 phosphorylation during chemical carcinogenesis will lead to a better understanding of the substantial roles of histone modifications in cancer development. To explore whether aberrant H3 phosphorylation contributes to chemical carcinogenesis, we examined the dynamic changes of H3 phosphorylation at various residues in chemical carcinogen-induced transformed human cells and human cancers. We found that histone H3 phosphorylation at Ser10 (p-H3S10) and Ser28 (p-H3S28) was up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Previous studies have reveals that NCAPH transcript is present in proliferating cells and preceded by phosphorylation of histone H3 at Ser‐10 . Various studies suggested that phosphorylation of histone H3 serine contributed to the HCC progression . Thus, we hypothesis that NCAPH could promotes HCC progression.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies have reveals that NCAPH transcript is present in proliferating cells and preceded by phosphorylation of histone H3 at Ser‐10 . Various studies suggested that phosphorylation of histone H3 serine contributed to the HCC progression . Thus, we hypothesis that NCAPH could promotes HCC progression.…”
Section: Discussionmentioning
confidence: 81%
“…15,16 Various studies suggested that phosphorylation of histone H3 serine contributed to the HCC progression. 17 and CFA assay. To further verify our results, we established NCAPHoverexpressing cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Further study confirmed that H3S10 phosphorylation provides a binding platform for the phospho-binding 14-3-3 proteins and histone acetyltransferase MOF to trigger acetylation of histone H4 at lysine 16 (H4K16ac), and H3S10 phosphorylation and H4K16ac further coordinatively regulate the binding site for bromodomain protein BRD4 (Zippo et al, 2009 ). Moreover, in addition to up-regulation of H3S10 phosphorylation in hepatocellular carcinoma and primary lung cancer (Zhu et al, 2016 ), there is sufficient evidence to prove that H3S10 phosphorylation is responsible for neoplastic cell transformation and oncogene c-fos/c-Jun activation (Choi et al, 2005 ), suggesting the important coordinative role between O -GlcNAcylation and other histone modifications in tumor development.…”
Section: Crosstalk Between O -Glcnacylation and Epmentioning
confidence: 99%
“…Scientific evidence has been emerging concerning the role of histone post-translational modifications in a multitude of DNA related processes, such as DNA damage repair, DNA replication, and transcription of tumor-related genes [51,52]. In particular, the dysregulation of histone H3 phosphorylation, reported following FA exposure, may perturb cellular pathways involved in human cancer development [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is known that in interphase cells, such phosphorylation phenomena are involved in the chromatin remodeling of the promoter regions of specific loci, i.e., FOS and JUN, implicated in tumorigenic processes, while in mitotic cells, they are responsible for the maintaining of chromosome stability and their accurate segregation [53]. Histone H3 phosphorylation was reported in aflatoxin B1-transformed hepatocytes, benzo(a)pyrene-and coke oven emissions-transformed human bronchial epithelial cells in which such modification performed a mediation role in cellular carcinogenic transformation [51]. The phosphorylation of H3S10 has been reported also to be induced by several environmental factors, such as arsenite [54], nickel [55], and UVB [56,57].…”
Section: Discussionmentioning
confidence: 99%